2020
DOI: 10.1038/s41598-020-76380-z
|View full text |Cite
|
Sign up to set email alerts
|

HSV-2 as a biomarker of HIV epidemic potential in female sex workers: meta-analysis, global epidemiology and implications

Abstract: This study investigated herpes simplex virus type 2 (HSV-2) seroprevalence utility as a predictor of HIV epidemic potential among female sex workers (FSWs) globally. We updated and analyzed a systematically-assembled database for paired HSV-2 and HIV seroprevalence measures among FSWs. The study identified 231 paired HSV-2/HIV prevalence measures from 40 countries. The pooled mean HIV prevalence using meta-analysis increased from 3.7% (95% CI 0.3–9.9%) among populations of FSWs with HSV-2 prevalence < 25% t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 35 publications
(70 reference statements)
0
6
0
1
Order By: Relevance
“…This search was conducted on August 16, 2022. Moreover, based on search terms used in a recent systematic review 8 and as informed by two decades of investigating the overlapping epidemiology of HSV-2 and HIV, 7 , 8 , 9 , 10 , 20 , 40 , 41 , 42 a narrative review was conducted of estimates for the contribution of HSV-2 to HIV transmission in Europe.…”
Section: Methodsmentioning
confidence: 99%
“…This search was conducted on August 16, 2022. Moreover, based on search terms used in a recent systematic review 8 and as informed by two decades of investigating the overlapping epidemiology of HSV-2 and HIV, 7 , 8 , 9 , 10 , 20 , 40 , 41 , 42 a narrative review was conducted of estimates for the contribution of HSV-2 to HIV transmission in Europe.…”
Section: Methodsmentioning
confidence: 99%
“…A meta-analysis showed that HSV-2 seropositivity is a risk factor for HIV infection among female sex workers. 25 The authors showed that compared with groups with an HSV-2 < 25%, the adjusted OR for HIV positivity was 2.8 when HSV-2 prevalence was 25% to 49%, and 13.4 when the HSV-2 prevalence was 75% to 100%. Therefore, the high prevalence of HSV-2 and coinfections among TGW in Central Brazil are a cause for concern and highlight the high burden of STIs in this minority population and the high risk of HIV spread.…”
Section: Discussionmentioning
confidence: 99%
“…Further, the study found a high prevalence of HSV-2 and HIV coinfection, HSV-2 and syphilis coinfection, and HSV-2, HIV, and syphilis triple infection among TGW living in Central Brazil. A meta-analysis showed that HSV-2 seropositivity is a risk factor for HIV infection among female sex workers 25 . The authors showed that compared with groups with an HSV-2 < 25%, the adjusted OR for HIV positivity was 2.8 when HSV-2 prevalence was 25% to 49%, and 13.4 when the HSV-2 prevalence was 75% to 100%.…”
Section: Discussionmentioning
confidence: 99%
“…No primeiro cenário, apresenta-se bem documentado na literatura a sinergia estabelecida entre os 2 patógenos (Chemaitelly et al, 2020). O HSV é responsável por intensificar e facilitar a disseminação do HIV, devido à sua capacidade de desenvolver processos inflamatórios e lesões ulcerativas na pele e mucosas, promovendo rupturas físicas, acumulando células como linfócitos T CD4+ e macrófagos, que podem ser infectadas pelo HIV, bem como abre portas de entrada para o mesmo (Johnston e Corey, 2016;Des jarlais et al, 2014;Sivarajah et al, 2017;Looker, et al, 2017).…”
Section: Características Do Hsv E Dados Clínicos Da Infecçãounclassified